An exploration into the rise in alcohol purchases and consumption by young black female working professional consumers in Bloemfontein South Africa. - Mokgele, Katlego Kefentse (The IIE, 2020)
As I write this I’m filled with plenty of emotions. I’m filled with the joy of completing my honours journey, the excitement of what’s to come, relief that comes with the pressures of finishing this paper, and even fear of what’s to come just to name a few. My journey towards completing my dissertation and my honours degree hasn’t been an easy one, It’s come with many challenges and a host of new experiences in a completely new environment. It is with great appreciation I want to thank and acknowledge all the individuals who helped me along this journey. First and foremost the strength which I receive from my spirituality. I want to thank my lecturer and supervisor Donna Berhardi for helping me through this treacherous path. My peers and friends for keeping me in positive spirits even when I was bleak. My family as a whole but specifically my parents My parents granted me the opportunity that very few individuals get, which is to pursue a postgraduate degree without the added stress of wondering how I was going to pay for school fees. Mom and Dad, this one for you. Thanks for pushing me towards higher education and seeing the light which wasn’t always clear. No words could ever express the gratitude I feel for the love and support I’ve received over the last two years. One day soon we’ll look back and think the signs to prosperity were always there.
Keywords: Advertising; Marketing; Liquor industry; Female empowerment; Femvertising; Purchasing behaviour; Consumer behaviour; Brand equity